Evidence for selection and spatially distinct patterns found in a putative zona pellucida gene in Pacific cod, and implications for management. Issue 23 (30th November 2021) - Spies, Ingrid; Drinan, Daniel P.; Petrou, Eleni L.; Spurr, Rory; Tarpey, Carolyn; Hartinger, Theodore; Larson, Wes; Hauser, Lorenz
Abstract: Genetic differentiation has been observed in marine species even when no obvious barriers to gene flow exist, and understanding such differentiation is essential for effective fisheries management. Highly differentiated outlier loci can provide information on how genetic variation might not only contribute to local adaptation but may also be affected by historical demographic events. A locus which aligned to a predicted zona pellucida sperm‐binding protein 3 gene (ZP3) in Atlantic cod ( Gadus morhua ) was previously identified as the highest outlier based on F ST in a RADseq study of Pacific cod ( Gadus macrocephalus ) across the West Coast of North America. However, because of the limited length of the RAD sequence and restricted geographic area of sampling, no conclusion on the functional significance of the observed variation was possible. In other marine species, ZP3 is involved in reproductive isolation, local adaptation, and has neofunctionalized as an antifreeze gene, and so it may provide important insights in functional population structure of Pacific cod. Here, we sequenced a 544‐bp region of ZP3 in 230 Pacific cod collected from throughout their geographic range. We observed striking patterns of spatial structuring of ZP3 haplotypes, with a sharp break near Kodiak, Alaska, USA where populations within 200 km of each other are nearly fixed for different haplotypes, contrasting a pattern of isolation by distance at other genetic markers in this region ( F ST = 0.003). Phylogenetic analysis of ZP3 haplotypes revealed that the more southern haplotypes appear to be ancestral, with the northern haplotype evolving more recently, potentially in response to a novel selective pressure as Pacific cod recolonized northern latitudes after glaciation. The sharp break in haplotype frequencies suggests strong selective pressures are operating on small spatial scales and illustrates that selection can create high divergence even in marine species with ample opportunities for gene flow. Abstract : We document a sharp break in haplotype frequencies for a putative sperm‐binding protein zona pellucida subunit 3 in Pacific cod. Results suggest strong selective pressures are operating on small spatial scales and illustrate that selection can create high divergence even in marine species with ample opportunities for gene flow.